PERFORMANCE ANALYSIS OF IEEE 802.15.4 CHANNEL ACCESS MECHANISMS DURING EVENT DETECTIONS IN WIRELESS SENSOR NETWORKS - Stephanie Imelda Pella; Hendro FJ Lami (Universitas Nusa Cendana, 2022)
The IEEE 802.15.4 protocol defines the medium access control layer of Zigbee, a widely implemented WSN technology. This protocol implements both the guaranteed time slot (GTS) scheme, where note request for slot(s) to transmit their packets collision-free and the contention-based scheme where nodes randomly draw a back-off counter to win channel access. This paper analyzes the performance of both schemes in WSNs when an event is detected and the packet arrival rate of the network increases using packet delivery ratio(PDR), network throughput and packet latency as the quality of service parameters. We consider various network densities (4, 9 and 16 nodes within a common transmission range). Simulations using Castalia 3.2 shows the GTS scheme has better PDR and latency than the contention-based scheme in the 4 and 9 nodes network. However, in a dense network (16 nodes), when the packet arrival rate increases, the contention-based scheme outperforms the GTS scheme.